The Use of the STAD Strategy to Promote Students’ Achievement in Science Education - Smiror Vann; Da BOU; Rorthmony Norm; Linna Nin; Borey Chhen (Gateway for Understanding Research in Education, 2026)
Science is a subject that requires teachers to apply teaching strategies that encourage students to work in groups, participate in answering questions, and create an active classroom environment that enhances learning outcomes. This study examined the effects of the STAD teaching strategy on students' achievement and engagement at 2 Thnou Primary School, Battambang, Cambodia. A quantitative design with a quasi-experimental approach was employed using two Grade 5 classes, selected through simple random sampling. The experimental group, which employed the STAD strategy, consisted of 51 students, and the control group, which received instruction using conventional techniques, consisted of 51 students. The researchers compared the mean scores of the two groups and evaluated changes in academic performance by analyzing pre- and post-tests. The researchers also used an observation checklist to monitor students' participation during STAD lessons. The results showed that the experimental group scored higher on average than the control group. Furthermore, the observations revealed that STAD enhanced students' engagement in cooperative activities, group discussions, and answering questions, leading to a more vibrant learning environment. The study indicates that using the STAD strategy can significantly enhance student engagement and academic achievement in science education. In conclusion, the STAD teaching strategy effectively improves learning outcomes and promotes active participation among Grade 5 students in science.